Taxonomic applicability of inflammatory cytokines in adverse outcome pathway (AOP) development. Issue 4 (16th February 2016) - Angrish, Michelle M.; Pleil, Joachim D.; Stiegel, Matthew A.; Madden, Michael C.; Moser, Virginia C.; Herr, David W.
ABSTRACT: Cytokines, low-molecular-weight messenger proteins that act as intercellular immunomodulatory signals, have become a mainstream preclinical marker for assessing the systemic inflammatory response to external stressors. The challenge is to quantitate from healthy subjects cytokine levels that are below or at baseline and relate those dynamic and complex cytokine signatures of exposures with the inflammatory and repair pathways. Thus, highly sensitive, specific, and precise analytical and statistical methods are critically important. Investigators at the U.S. Environmental Protection Agency (EPA) have implemented advanced technologies and developed statistics for evaluating panels of inflammatory cytokines in human blood, exhaled breath condensate, urine samples, and murine biological media. Advanced multiplex, bead-based, and automated analytical platforms provided sufficient sensitivity, precision, and accuracy over the traditional enzyme-linked immunosorbent assay (ELISA). Thus, baseline cytokine levels can be quantified from healthy human subjects and animals and compared to an in vivo exposure response from an environmental chemical. Specifically, patterns of cytokine responses in humans exposed to environmental levels of ozone and diesel exhaust, and in rodents exposed to selected pesticides (such as fipronil and carbaryl), were used as case studies to generally assess the taxonomic applicability of cytokine responses. The findings in this study may aid in the application of measureable cytokine markers in future adverse outcome pathway (AOP)-based toxicity testing. Data from human and animal studies were coalesced and the possibility of using cytokines as key events (KE) to bridge species responses to external stressors in an AOP-based framework was explored.